Airborne bacteria in a wastewater treatment plant: Emission characterization, source analysis and health risk assessment. (1st February 2019) - Yang, Kaixiong; Li, Lin; Wang, Yanjie; Xue, Song; Han, Yunping; Liu, Junxin
Abstract: Wastewater treatment plants (WWTPs) are major sources of airborne bacteria, which could pose health risks to WWTP workers and surrounding residents. In this study, air samples were collected from various treatment facilities of a typical WWTP. Community compositions of airborne bacteria were identified by high-throughput sequencing technique. SourceTracker was used to determine the percentages of airborne bacteria from wastewater, sludge, ambient air, and other environment. Health risks associated with airborne bacteria were estimated based on the average daily dose rates (ADD) of exposure by inhalation and skin contact. Concentrations of airborne bacteria varied in a wide range of 23–4878 CFU/m 3 . The main emission sources of airborne bacteria were treatment facilities with aeration, mechanical agitation, and located indoors. For treatment facilities located indoors, higher percentages of airborne bacteria were associated with wastewater and sludge, while more airborne bacteria were originated from the ambient air for outdoor installations. Opportunistic pathogens such as Micrococcus, Bacteroides, Chryseobacterium, Pseudomonas, and Acinetobacter, were detected in airborne bacteria. Inhalation was the main pathway for on-site workers exposure to airborne bacteria. Due to the presence of opportunistic pathogens, strict control measures should be employed in WWTPs to reduce the infection risks. Graphical abstract: Image 1 Highlights: High levels of airborne bacteria were found in a typical WWTP. Characterization of outdoor and indoor airborne bacteria presented distinctions. Sources of airborne bacteria were identified by SourceTracker method. Higher proportion of indoor airborne bacteria originated from wastewater and sludge. Pathogens were detected and inhalation was the main exposure pathway.